Comparative Analysis of Water and Oil Media on Temperature Stability in PID Control-Based Digital Thermometer Calibrator - Sofyan, Mochammad; Syaifudin, Syaifudin; Pudji, Andjar; Utomo, Bedjo; Nugraha, Anggara Trisna (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2023)
Digital thermometers are measuring instruments needed to perform temperature measurement actions and must be calibrated periodically according to standard measurement methods. The purpose of developing this tool is to add PID control to the calibration media where PID control aims to regulate the stability of the temperature setting to be achieved. This is achieved by studying and evaluating the effect of temperature stability on the heater and LM35DZ temperature sensor. This research method uses the Arduino Nanosystem for data processing and PID system control. The LM35DZ temperature sensor on the heater is regulated by a 2 Channel SSR module using a PID system then the temperature generated by the heater will be read by the LM35DZ and displayed on the LCD. The results of this study, digital thermometer calibrator measurements have been successfully carried out by comparing 3 digital thermometers with different brands, namely Omron 343F, Omron 245, and ThermoOne. The difference in error values in oil media is 3-4% and in water media 2-4% with the value of time stability in water media for 3-3.3 minutes and in oil media for 1-2 hours. With this comparison of calibration media, it is hoped that it can help in measuring temperature with better and more effective results. find methods, results, conclusions.